Tau Knockout and α-Synuclein A53T Synergy Modulated Parvalbumin-Positive Neurons Degeneration Staging in Substantia Nigra Pars Reticulata of Parkinson’s Disease-Liked Model - Zheng, Meige; Liu, Yanchang; Xiao, Zhaoming; Jiao, Luyan; Lin, Xian (Frontiers in Aging Neuroscience, 2022)
Besides the massive loss of dopaminergic neurons in the substantia nigra pars compacta (SNC), the activity of parvalbumin-positive (PV+) neurons in the substantia nigra pars reticulata (SNR) could also be affected in Parkinson's disease (PD). We previously showed that the Pitx3-A53T α-Syn × Tau−/− triple transgenic mice model of PD exhibited anxiety-like behavior from 12 to 18-mouth-old, that may be associated with the substantial degeneration of PV+ neurons in the SNR. However, the mechanism by which this occurs remains unknown. Here, we demonstrated that, as compared with non-transgenic (nTg) mice, the accumulation of α-synuclein in the SNR of aged Pitx3-A53T α-Syn × Tau−/− mice was increased obviously, which was accompanied by the considerable degeneration of PV+ neurons and the massive generation of apoptotic NeuN+/TUNEL+ neurons. Interestingly, PV was not costained with TUNEL, a marker of apoptosis. PV+ neurons in the SNR may undergo a transitional stage from decreased expression of PV to increased expression of NeuN and then to TUNEL expression. In addition, the degeneration of PV+ neurons and the expression of NeuN were rarely observed in the SNR of nTg and the other triple transgenic mice. Hence, we propose that NeuN may be suit for an indicator which suggests degeneration of PV+ neurons in the SNR, and the molecular mechanism is worthy of further research.